THE IMPORTANCE OF PREVENTIVE MEASURES IN EARLY DIAGNOSIS AND PREVENTION OF DISEASE RECURRENCE AMONG WOMEN OF REPRODUCTIVE AGE WITH BRONCHIAL ASTHMA (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Asthma is a common and potentially life-threatening chronic respiratory condition that frequently complicates pregnancy and poses significant risks to both maternal and fetal health when inadequately controlled. This review integrates evidence from clinical trials, observational studies, systematic reviews, meta-analyses, and international guideline recommendations to provide a comprehensive overview of asthma in pregnancy. Physiological adaptations during gestation, including changes in respiratory mechanics, immune regulation, and hormonal balance, can alter asthma severity and contribute to an increased risk of exacerbations, particularly during early and late pregnancy. Approximately two-fifths of pregnant women experience worsening asthma symptoms, which are associated with adverse obstetric and neonatal outcomes such as hypertensive disorders of pregnancy, gestational diabetes, fetal growth restriction, preterm birth, and cesarean delivery. Maternal comorbidities, including obesity, depression, and metabolic disorders, as well as environmental and nutritional factors, further modify disease control and pregnancy outcomes. Importantly, current evidence indicates that most standard asthma therapies, including inhaled corticosteroids, bronchodilators, and selected biologic agents, are safe and effective during pregnancy. Optimal asthma management relies on individualized treatment strategies, regular monitoring, patient education, and multidisciplinary care to minimize risks and improve both short- and long-term outcomes for mothers and their offspring.
Keywords: Asthma in pregnancy; Maternal asthma control; Pregnancy outcomes; Asthma exacerbations; Pharmacological safety; Perinatal risk factors; Childhood asthma; Multidisciplinary care